AB0369 SAFETY, EFFICACY AND RETENTION RATE OF BIOLOGIC DISEASE MODIFYING ANTI-RHEUMATIC DRUGS (BDMARDS) IN ASSOCIATION WITH DENOSUMAB: COMPARISON OF COMBINATION AND MONO-THERAPY REGIMENS. (June 2019) - Bruni, Cosimo; Cigolini, Cosimo; Tesei, Giulia; Bartoli, Francesca; Fiori, Ginevra; Conforti, Maria Letizia; Randone, Silvia Bellando; Guiducci, Serena; Matucci-Cerinic, Marco
Abstract : Background: Osteoporosis is a frequent complication of rheumatic muscle-skeletal diseases (RMD), with high impact from steroid treatment. It is known that bDMARD impact positively on patients' prognosis and this is also known for Denosumab, a monoclonal antibody for osteoporosis. The combination treatment with two monoclonal antibodies, bDMARD & denosumab, has addressed the problem of safety and efficacy, with incomplete answers from the available literature. Objectives: to evaluate the impact of the combination treatment bDMARD+Denosumab (COMBO group), compared to mono-therapy with bDMARD (MONO group), on clinical efficacy, safety and treatment retention of bDMARD in patients with RMD. Methods: RMD patients treated with COMBO therapy where enrolled from a single centre rheumatology unit; for each case, at least one MONO therapy control (matched per age±5 years, sex, bDMARD, RMD, without osteoporosis) was enrolled. Data on clinical efficacy (3-points Likert scale for physician and patient – improved/stable/worse), safety (locl reaction, serious and non-serious adverse events) and bDMARD treatment retention at 12, 18 and 24 months. Results: Out of 129 eligible patients, 77 were enrolled in the protocol: 49 in the MONO and 28 in the COMBO group. The two groups were different of age (slightly higher in the COMBO group), for tender joint count, erythrocyte sedimentation rate and c-reactive protein (higher in the MONO group). Efficacy analysis showed higher percentage of clinical improvement at 12 months in the MONO group at 12 months, being not significant at 18 and 24 months (possibly explained by a different disease activity at baseline visit, corresponding to the overlap of denosumab on top of bDMARD in the COMBO and to the initiation of bDMARD in the MONO group). Between the 2 groups, no difference about safety and retention rate was found. Conclusion: the efficacy of COMBO treatment is similar to MONO therapy. Moreover, the data show that also safety and retention rate are similar. Therefore, the COMBO treatment with 2 different monoclonals can be safely employed in the treatment of RMDs and osteoporosis. Disclosure of Interests: Cosimo Bruni: None declared, Cosimo Cigolini: None declared, Giulia Tesei: None declared, Francesca Bartoli: None declared, Ginevra Fiori: None declared, Maria Letizia Conforti: None declared, Silvia Bellando Randone: None declared, Serena Guiducci: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Pfizer, BMS, Chemomab, Sanipedia, Speakers bureau: Actelion, BMS; MSD, Janssen